Carotid artery diameter assessment in men and women and the relation to age, sex and body mass index using ultrasonography - Ojaare, Magaji G.; Annongu, Terkimbi I.; Msuega, Chia D.; Mohammad, Hameed O.; Farati, Abubakar; Alexander, Angbalaga; Umer, Bulus P. (International Journal of Advances in Medicine, 2021)
Background: Carotid artery dimensions are increasingly used for detecting early atherosclerosis and predicting clinical complications. Aim was to explore relationships between gender, age and body mass index (BMI) and the diameters of the common carotid artery (CCA) and internal carotid artery (ICA) using ultrasonography. Methods: This was a cross-sectional study carried out at the University of Maiduguri Teaching Hospital between February-October, 2011. The 400 adult males and females above 18 years underwent carotid artery ultrasonography for measurement of the IMT of the common and internal carotid arteries. The influence of age, sex, weight, height, and the basal metabolic index (BMI) was investigated. Results: There were 239 (59.80%) males and 161 (40.20%) females aged between 18 to 81 years (Mean±SD, 36.74±14.79 years). The mean±SD diameters for right common carotid artery (RCCA) and left common carotid artery (LCCA) were 6.39±0.71mm and 6.28±0.74mm respectively. The right internal carotid artery (RICA) and left internal carotid artery (LICA) had mean±SD diameters of 4.63±0.63 mm and 4.61±0.63 mm respectively. The luminal diameters of the carotid arteries increased significantly with age and increased BMI. The luminal diameters of the CCA and ICA were significantly smaller in women than in men. Conclusions: Common carotid and internal carotid artery luminal diameter tends to be larger in men than women among adults and increases with age and BMI. There is no difference in the luminal diameter between the left and right carotid artery.